CPEC Development Effect on Business Improvement: A Mediating Role of Educational, Employment Concerns, Healthcare Facilities in the Rashakai Special Economic Zone - Mehmood, Faisal; Bing, Wang; Henna; Ullah, Nazir; Hussain, Naqeen (The journal of contemporary issues in business and government, 2021)
While the Belt and Road Initiative (BRI) has brought substantial benefits to participating countries, it has also increased the risk of confrontation between international projects and local people. Despite this, there is still a gap in knowledge about how CPEC development could bring changes in the education, employment opportunities, healthcare facilities concerning the business improvement in the special economic zone to local residents. In the China-Pakistan Economic Corridor (CPEC) context, this research utilises a quantitative method with (SEM) to explain the predictive effect of CPEC development on education, employment, healthcare facilities, and special economic zone. The sample size was (n=399) with the formula of Taro Yamane, and a purposive sampling technique was applied. The CPEC project long-term motivation is to spark education, employment, and healthcare facilities initiatives. The comprehensive CPEC development activities are managed to improve special economic zones and exclusively focus on the local community’s long-term sustainability. Therefore, education, health care, and employment opportunities will improve significantly once the CPEC project is completed. Theoretically, this research adds to the body of CPEC development knowledge, and it also interrelates factors such as employment concerns, educational concerns, healthcare facilities, and special economic zones under the CPEC project. It is recommended that the work on the CPEC project should speed up with the collaboration of the Pakistan government.